Strategi Pengembangan Objek Wisata Berbasis Collaborative Governance Di Desa Agusen - Habibi, Jara; Hajar, Siti; Bida, Obed (Jurnal ilmiah Manajemen Publik dan Kebijakan Sosial, 2023)
Tourist attractions in Agusen Village have their own characteristics and attractions that are able to produce excellence and contribute to the economy of local and regional communities. However, the development of tourist attractions in Agusen Village is still not optimal and has not been well managed, especially facilities and infrastructure such as parking lots, prayer rooms, water facilities and abandoned huts as well as road access to tourist attractions. This is the main problem in developing tourist attractions in Agusen Village, so it really requires collaboration and cooperation with several parties, especially the government, community and business actors to be able to build and develop tourist attractions in Agusen Village through the Collaborative Governance concept. The aim of this research is to analyze the Collaborative Governance-based tourist attraction development strategy in Agusen Village, and the research method used is a qualitative method. This research shows that the development of tourist attractions in Agusen Village must also be supported by parties who are directly and actively involved in tourism activities. The collaboration system is a strategy that can be applied to create superior and competitive tourist attractions by fostering cooperation and partnerships as regulated in applicable regulations. The cooperation system implemented in developing tourist attractions in Agusen Village can be carried out professionally and actions are based on ideas or thoughts which is a continuous process so that it can involve all parties to develop existing resources including increasing the capacity of human resources.